First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations and health, the statistics relating to infant mortality, defective children, the death-rate from tuberculosis, the ravages of venereal diseases, and the rejection of a million men as unfit for the Army would be diminished in a short time by more than one-half. It was lamentable that the powers which existed in the Public Health and other Acts should have been so inadequately carried into effect. What was needed was to create and concentrate a driving force of public opinion, which would not be denied, and to that task they were setting their hands. It was doubtful whether so many eminent medical men were ever included in any body outside their own professional organisations as were to be found on the Medical Council of the League. It only remained for the public to support those experts. SIR ALFRED FRIPP emphasised the fact that there was no intention to rival the activities of existing agencies, or to act in opposition to the Government. The idea of the League was to centralise and co-ordinate all effort, and he suggested that the present offered a rare opportunity of educating the people in matters of health, for the public mind was in a receptive state. Miss OLGA NETHERSOLE said that in her study of her art she did not go to books or to the theatres, but to the highways and byways of life. She visited prisons, workhouses, asylums, and Courts of Justice, and her observations led her to the conclusion that the greatest factors in the establishment of many of the evils which were deplored were heredity and environment. During the war she helped to compile the national register, and in that part of the borough of Southwark which was assigned to her she was ashamed to find conditions so insanitary and unhygienic existing close to the Houses of Parliament and to the Palace that she determined to establish a People's League of Health when the war was over. They had it on the authority of Sir George Newman that a million children were so mentally and physically defective as to be unable to derive reasonable benefit from the education provided for them by the ratepayers. There had been unrest recently in the ranks of Labour, and this she regarded as a healthy sign, because resentment was at least antagonistic to stagnation, which meant disease and death. The health of a nation was its greatest asset, and to attain it the first need was proper housing, with hot water laid on at the mains. Next the Legislature should secure the medical supervision of young people during the critical ages between 14 and 18 years. No child between those ages should be employed for profit without having a certificate of fitness from the local Medical Officer of Health, who should re-examine the young person every three months. In conclusion, she pleaded that medical scientists should be given a chance to see what they could do to improve national conditions. Lawyers had tried, and had had it all their own way; if the medical experts were given an equal chance she had no fear of the result. The meeting was addressed also by Dr. ERIC PRITCHARD, of the National Baby Week Council, who urged the need of improving the homes and the mothers of the race; Mrs. BOOTH, of the Salvation Army, who said that experience gained in working among the poor in London and throughout the Empire convinced her that the evils against which the League should direct its efforts were first, strong drink, next overcrowding, next over-pressure in schools, and next the neglect of motherhood; Mr. E.B. TURNER, the chairman of the Medical Committee of the National Council for Combating Venereal Disease, who pointed out how much had been done to diminish the incidence of such disease in the Army by the organisation of sports and means of healthy amusement, and urged that similar provision should be made for the youthful civil population; Miss DAMER DAWSON, the chief of the Women's Police Service, who expressed a wish that every village should have a good cinema hall, and that trained women should supervise the public parks and playgrounds of the children ; Dr. STANCOMB, of Southampton, and LORD WILLOUGHBY DE BROKE, who hoped that pressure would be put upon the Ministry of Health to carry out the purpose for which it was established, and that they would be on their guard against making health a question of votes. Reprinted from THE TIMES, May 12th, 1920. "WRONG TO BE ILL." 14,000,000 WORK WEEKS LOST IN A YEAR. A meeting of the People's League of Health was held at the Mansion House yesterday, when members of the Medical Council addressed the Lord Mayors and Mayors of the country. COLONEL C.J. BOND, of Leicester, Vice-Chairman of the Medical Consultative Council of the Ministry of Health, spoke of the facts revealed by the national inquiry into the physical state of the male population of military age, which, he said, showed that out of 2½ million men examined in 1918 only one in three attained the standard of Grade 1. Loss of health and physical vigour not only affected military service, but had also an intimate bearing on the industrial efficiency of the population. Some 14 million "work weeks" were lost to the nation annually through sickness among insured workers, an 45 200/B/3/2/C693/1/71